TOPK modulates tumour-specific radiosensitivity and correlates with recurrence after prostate radiotherapy - Pirovano, G; Ashton, T; Herbert, K; Bryant, R; Verrill, C; Cerundolo, L; Buffa, F; Prevo, R; Harrap, I; Ryan, A; Macaulay, V; McKenna, W; et al. (Cancer Research UK, 2017)
Background: Tumour-specific radiosensitising treatments may enhance the efficacy of radiotherapy without exacerbating side effects. In this study we determined the radiation response following depletion or inhibition of TOPK, a MAPKK family Ser/Thr protein kinase that is upregulated in many cancers. Methods: Radiation response was studied in a wide range of cancer cell lines and normal cells using colony formation assays. The effect on cell cycle progression was assessed, and the relationship between TOPK expression and therapeutic efficacy was studied in a cohort of 128 prostate cancer patients treated with radical radiotherapy. Results: TOPK knockdown did not alter radiation response in normal tissues, but significantly enhanced radiosensitivity in cancer cells. This result was recapitulated in TOPK knock-out cells and with the TOPK inhibitor, OTS964. TOPK depletion altered the G1/S transition and G2/M arrest in response to radiation. Furthermore, TOPK depletion increased chromosomal aberrations, multinucleation and apoptotic cell death after irradiation. These results suggest a possible role for TOPK in the radiation-induced DNA damage checkpoints. These findings have clinical relevance, as elevated TOPK protein expression was associated with poorer clinical outcomes in prostate cancer patients treated with radical radiotherapy. Conclusion: This study demonstrates that TOPK disruption may cause tumour-specific radiosensitisation in multiple different tumour types.